P200 Snoring and carotid atheroma: no association. (16th November 2010) - Mason, R H; Mehta, Z; Rothwell, P M; Stradling, J R
Abstract : Background: Obstructive Sleep apnoea (OSA) has increasingly been linked to cardiovascular endpoints including hypertension, stroke, myocardial infarction, and carotid atherosclerosis. Snoring is strongly associated with OSA. More recently, the snoring component of OSA, by producing local arterial trauma, has been independently linked to the presence of carotid but not femoral atheroma, 1 and to acute carotid trauma in an animal model.2 The aim of this study was to identify whether this relationship could be established retrospectively in a high vascular risk cohort of individuals with a recent cerebrovascular event (TIA or stroke). Method: Participants with a recent TIA or stroke in the Oxford Vascular Study (OXVASC) completed an entry questionnaire which included frequency of snoring (never, rarely (1–2/year), occasionally (4–8/year), sometimes (1–2/month), often (1–2/week), usually (3–5/week) and always (every night). A subset of 316 individuals (aged 62–84 years), with both a completed snoring questionnaire and carotid Doppler data, were included. This information was used to retrospectively assess a potential relationship between presence and severity of snoring, and degree of carotid artery stenosis and plaque type (echogenic/echolucent/mixed, calcified/non-calcified and smooth/irregular). Results: 160 out of 316 participants were male, mean (SD) age 73.2 (11.22). No significant association could be identified between intensity of self-reported snoring and degree of carotid stenosis or plaque morphology. Conclusions: No significant association could be identified between snoring and carotid atheroma. There are no obvious explanations for the discrepancy between this study and previous work, except that the original study measured snoring objectively during a one night in hospital study, whereas in our study snoring was subjectively assessed and perhaps better represents the usual situation at home. Furthermore, the femoral artery may not be an appropriate 'control' artery with which to compare the carotid for atheroma.